Effect of two teaching methods on student’s achievement in junior secondary school social studies in Ibadan metropolis (2018)
The research investigates effects of two teaching methods of students of Junior Secondary Schools within Ibadan Metropolis. Multistage sampling techniques were adopted in selecting three Local government Areas, Six Junior Secondary Schools, 12 Teachers and 188 Students. Seven hypotheses stated and tested with four validated instruments: Social Studies Achievement Test, Teaching Techniques Questionnaire, Study Habits Rating Scale and Social Studies Attitudinal Scale, guided the study. Data obtained were analysed using Analysis of Covariance (ANCOVA) at 0.05 level of significance. Results shows that the main effect of treatment (Brainstorming and Project Methods) is significant on students’ achievements in Social Studies (F= 4.422; P < 0.05); the main effect of gender is significant on students’ achievements in Social Studies (F= 5.663; P < 0.05); the main effect of study habit was significant on students’ achievements in Social Studies (F= 3.393; P < 0.05); the interaction effect of treatment and gender was significant on students’ achievements in Social Studies (F= 2.076; P < 0.05); the interaction effect of gender and study habit was significant on students’ achievements in Social Studies (F= 2.523; P < 0.05); the interaction effect of treatment, gender and study habit was significant on students’ achievements in Social Studies (F= 2.198; P < 0.05). The paper therefore recommends that Social Studies teachers should make it as a point of duty to always employ brainstorming teaching method in teaching and learning process to enhance students’ desirable achievement.